Role of atmospheric pollution on the natural history of idiopathic pulmonary fibrosis. Issue 2 (10th August 2017) - Sesé, Lucile; Nunes, Hilario; Cottin, Vincent; Sanyal, Shreosi; Didier, Morgane; Carton, Zohra; Israel-Biet, Dominique; Crestani, Bruno; Cadranel, Jacques; Wallaert, Benoit; Tazi, Abdellatif; Maître, Bernard; et al.
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) has an unpredictable course corresponding to various profiles: stability, physiological disease progression and rapid decline. A minority of patients experience acute exacerbations (AEs). A recent study suggested that ozone and nitrogen dioxide might contribute to the occurrence of AE. We hypothesised that outdoor air pollution might influence the natural history of IPF. Methods: Patients were selected from the French cohort COhorte FIbrose (COFI), a national multicentre longitudinal prospective cohort of IPF (n=192). Air pollutant levels were assigned to each patient from the air quality monitoring station closest to the patient's geocoded residence. Cox proportional hazards model was used to evaluate the impact of air pollution on AE, disease progression and death. Results: Onset of AEs was significantly associated with an increased mean level of ozone in the six preceding weeks, with an HR of 1.47 (95% CI 1.13 to 1.92) per 10 µg/m 3 (p=0.005). Cumulative levels of exposure to particulate matter PM10 and PM2.5 were above WHO recommendations in 34% and 100% of patients, respectively. Mortality was significantly associated with increased levels of exposure to PM10 (HR=2.01, 95% CI 1.07 to 3.77) per 10 µg/m 3 (p=0.03), and PM2.5 (HR=7.93, 95% CI 2.93 to 21.33) per 10 µg/m 3 (p<0.001). Conclusion: This study suggests that air pollution has a negative impact on IPF outcomes, corroborating the role of ozone on AEs and establishing, for the first time, the potential role of long-term exposure to PM10 and PM2.5 on overall mortality.